Geoeconomics, Connectivity, and Strategic Partnership: Iran and Armenia in Eurasia’s New Order - Mirfakhraei, Seyed Hassan (YSU Journal of International Affairs, 2025)
The geoeconomics of Eurasia has been constantly evolving over the past decade. Various events have contributed to these changes, including the outbreak of war in Ukraine, sanctions on Russia’s geoeconomic infrastructure, shifts in the status of the Caspian Sea, and geopolitical developments in the South Caucasus. These transformations have created new conditions in Eurasian geoeconomic dynamics, prompting many stakeholders in the South Caucasus to redefine their geoeconomic roles. Iran’s new engagements in this field are defined within the framework of the Eurasian Economic Union (EAEU) and the Shanghai Cooperation Organization (SCO). Armenia, as a neighboring country with extensive historical ties to Iran, is considered a key player in the South Caucasus and a strategic partner for Iran. Under the new regional conditions, and in response to emerging uncertainties, Armenia serves as an important and reliable access route, especially for Iran–Russia geoeconomic interactions. Trade opportunities and energy cooperation can further deepen these interactions. A strategic partnership offers a low-cost, long-term framework for advancing mutual interests. It must include specific conditions, focus on priority sectors, and align with the interests of Iran and Armenia, as well as broader regional trends.